Prevalence of chronic obstructive pulmonary disease with breathlessness in Australia: weighted using the 2016 Australian census. Issue 5 (27th May 2021) - Toelle, Brett G.; Ampon, Rosario D.; Abramson, Michael J.; James, Alan L.; Maguire, Graeme P.; Wood‐Baker, Richard; Johns, David P.; Marks, Guy B.
Abstract: Access to up‐to‐date Australian disease prevalence estimates assists health services and consumer organisations to plan and allocate resources. The Burden of Obstructive Lung Disease study was conducted between 2006 and 2012 and provided chronic obstructive pulmonary disease (COPD) (post‐bronchodilator airflow limitation) prevalence estimates weighted to the 2006 Australian census. Using the 2016 Australian census, an updated prevalence estimate of all COPD is 8.30% (95% confidence interval = 6.59%–10.01%) for adults aged 40 or more years in Australia and includes 2.52% with mild breathlessness, 0.99% with moderate breathlessness and 0.91% with severe breathlessness.